Aflatoxin contamination in feeds and feed ingredients from Lampung and East Java provinces - Sjamsul Bahri; R Maryam; R Widiastuti (Indonesian Center for Animal Research and Development (ICARD), 2005)
In the last few years, poultry industries (broiler and laying hens) in Indonesia are faced on several problems, vaccination for instance, which suspected relate to highly-contaminated aflatoxins in feeds. The aim of this study is to give recent information on aflatoxin contamination in feeds, feed ingredients, and foods originated from some districts in Lampung and East Java provinces. The results of the study indicated that the percentage of aflatoxin B1 contamination in corn, commercial feeds, and peanuts in Lampung were 86.7, 70.0 and 80.0% with the average levels of 31.5, 13.5 and 32.2 μg/kg, respectively. Low levels of the other aflatoxins (AFB2, AFG1, and AFG2) were also detected in the samples. The highest percentage of aflatoxin contamination was found in samples from retailer (100%), followed by samples from traditional markets (91.7%), poultry shops (76.9), and a feed company (33.3%). The average levels of aflatoxin found were 58.8, 34.3, 17.8 and 2.9 μg/kg, respectively. In East Java, AFB1 was detected in all samples (corn, rice bran, concentrate and commercial feeds) on the average levels of 25.4, 69.7, 134.2 and 30.7 μg/kg respectively. The levels of AFG1 on the samples from East Java were much more higher than those of from Lampung, as well as the percentage. Key Words: Aflatoxins, Feed, Feed Ingredients, Lampung, East Java